Weight loss in a UK commercial all meal provision study: a randomised controlled trial - Mellor, D.D.; Whitham, C.; Goodwin, S.; Morris, M.; Reid, M.; Atkin, S.L. (2013)
Background: Effective approaches are needed to address the increasing prev- alence of overweight and obesity. The present study investigated whether all meal provision was a more effective and acceptable method for weight loss than a self-directed diet. Methods: This randomised controlled trial recruited 112 men and women with a body mass index in the range 27–35 kg m–2, who had no comorbidi- ties, from the local area of Hull. Participants were randomised to receive either meal provision or follow a self-directed diet for a 12-week period that resulted in an estimated 2928 kJ day␣1 (700 kcal day␣1) deficit. A dietitian supervised both dietary interventions. Results: At 12 weeks [mean (SEM)], percentage weight loss in the meal provision group was 6.6% (0.5%) compared to 4.3% (0.6%) for those on the self-directed diet. In terms of clinically relevant weight loss, 61% of par- ticipants lost 5% or more of their body weight with meal provision com- pared to 22% on the self-directed diet (P < 0.001). Weight loss was associated with wellbeing in both groups. Attrition was less apparent with 7% of those participants receiving meal provision withdrawing from the study compared to 41% of those following the self-directed diet (P < 0.001). Conclusions: Meal provision was a more effective and accepted method for weight loss over a 12-week period compared to a self-directed diet. This may in part represent the difference between being given the meal provision food free of charge. However, longer-term maintenance studies need to be undertaken to ascertain their effects on the maintenance of weight loss.